Tax system characteristics and country-level differences in earnings management - Simon Helms; Reinald Koch; Till B. Scheider (Journal of Business Economics, 2025)
We examine the extent to which European listed firms use deferred tax accounting to manage their GAAP earnings in order to meet financial analysts' earnings forecasts. The cross-country nature of our data allows us to compare the use of this earnings management channel across countries and to relate these differences to certain country characteristics, in particular country-specific features of the tax system. Our results clearly document that European listed firms use deferred tax assets to inflate earnings when pre-manipulated earnings fall below the average analyst forecast. On average, they increase their return on assets by 0.2 percentage points (or 3 percent) through this channel. Our results also show a large variation in this effect across countries. Firms that face larger deviations between tax and financial accounting, higher tax rates, a stricter tax enforcement and a more lenient tax loss offset may, to some extent, make greater use of this earnings management channel.
Keywords: H25; M41; 650; Earnings management; Deferred tax accounting; Tax law; Tax strategy